2009
DOI: 10.1101/gad.522509
|View full text |Cite
|
Sign up to set email alerts
|

Trans-acting antisense RNAs mediate transcriptional gene cosuppression in S. cerevisiae

Abstract: Homology-dependent gene silencing, a phenomenon described as cosuppression in plants, depends on siRNAs. We provide evidence that in Saccharomyces cerevisiae, which is missing the RNAi machinery, protein coding gene cosuppression exists. Indeed, introduction of an additional copy of PHO84 on a plasmid or within the genome results in the cosilencing of both the transgene and the endogenous gene. This repression is transcriptional and position-independent and requires trans-acting antisense RNAs. Antisense RNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
138
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(152 citation statements)
references
References 46 publications
11
138
1
2
Order By: Relevance
“…Accumulation of these ncRNAs, called XUTs, in the absence of 5′-3′ exoribonuclease activity could explain the down-regulation of the expression of specific genes. This model also relies on previously published work in which it was demonstrated that the expression of the PHO84 and TY1 genes can be down-regulated by the accumulation of antisense transcripts that are substrates of the exoribonucleases Rrp6 and Xrn1, respectively (28)(29)(30). We therefore checked to see whether any of the genes corresponding to the down-regulated proteins in our 2D gel analysis also contained potential XUTs (16), but did not find any.…”
Section: Table 1 Dcs Family Proteins and Activation Of Exoribonucleamentioning
confidence: 83%
“…Accumulation of these ncRNAs, called XUTs, in the absence of 5′-3′ exoribonuclease activity could explain the down-regulation of the expression of specific genes. This model also relies on previously published work in which it was demonstrated that the expression of the PHO84 and TY1 genes can be down-regulated by the accumulation of antisense transcripts that are substrates of the exoribonucleases Rrp6 and Xrn1, respectively (28)(29)(30). We therefore checked to see whether any of the genes corresponding to the down-regulated proteins in our 2D gel analysis also contained potential XUTs (16), but did not find any.…”
Section: Table 1 Dcs Family Proteins and Activation Of Exoribonucleamentioning
confidence: 83%
“…In this case, antisense transcription was found to result in the recruitment of the histone deacetylase Hda1 and thereby downregulate the authentic PHO84 promoter (Camblong et al 2007). Importantly, antisense at PHO84 was found to act both in cis and in trans, as shown by ectopic expression of the antisense and use of a ribozyme inserted in the antisense sequence to cleave the antisense after its synthesis (Camblong et al 2009). In a third study carried out on the KCS1 locus, both antisense and intragenic transcripts were detected (Nishizawa et al 2008).…”
Section: Regulation By Noncoding Rnasmentioning
confidence: 99%
“…Finally, as more efforts are put forth to decipher the role of the non-coding genome, it must be emphasized that some of these long non-coding RNAs have been detected with translating ribosomes. 88 Although no examples of lncRNAs that produce functional peptides have been documented to date, we should continue to view the term 29 Promotes induction MMF1 Mitochondrial protein YES ASP3 lncRNA 98 Upregulation ASP3 Asparagine catabolism YES PHO84 AS RNA [99][100][101] Repression PHO84 Phosphate metabolism YES SRG1 28,50,51 Repression SER3 Serine / glycine biogenesis YES PHO5 AS RNA 102 Promotes induction PHO5 Phosphate metabolism YES usURA2. 103 Repression URA2 Pyrimidine biogenesis YES usDCI1.…”
mentioning
confidence: 99%